Pengembangan Media Diorama Tema Ekosistem Untuk Kelas V Sekolah Dasar - Dara Cyntia Wijaya; Dea Mustika (Civiliza Publishing, 2022)
The purpose of this study is to describe the development of ecosystem theme diorama media for class V SD Negeri 011 Sorek Satu Pelalawan Regency. This research method uses development research with the ADDIE development model. This research was conducted in four stages, namely 1) the analysis stage consists of needs analysis, educator analysis, student analysis, curriculum analysis, and learning material analysis; 2) the design stage, namely designing a diorama with the theme of the Indonesian rainforest ecosystem; 3) the development stage, namely the process of making the design objective. The results of this study indicate that the ecosystem theme diorama media meets the very valid criteria. The media experts obtained an average result of 94% with a very valid category and declared fit for use. In the validation of the material obtained an average result of 97% with a very correct category which was declared suitable for use without revision by conducting the validation test twice; 4) the practicality of the diorama media is seen from the results of the implementation of the results of the student response questionnaire assessment by obtaining 97% results in the convenient category. In the fifth-grade teacher's response questionnaire, an average result of 97% was obtained in the convenient category.